Ressignificando linguagens no espaço escolar: esboçando um outro mapa para leitura e escrita de textos - Vilha, Evaristo Ferreira (2007)
The called dissertation re-meaning languages at the school space: sketching another map for reading and writing texts, looks for sketch another context to do it pedagogic in which it has the deepest and possible immersion in Technologies of Digital Communication, through the pupils have free access to the cyberspace, and also that they are acting as protagonists in the expansivity of hypertext. It search to not only rethink the reading that those deriving ones of the didactic book, it worries about the low levels of letterment demonstrated even though for the students who conclude High School, and considers that the pupils can be adapt of the varied plateaus of the textuality, between them the cohesion and literal coherence and, always in the possible measure do, a deepening in the domain of the linguistic mechanisms of the argumentatives operators, the modalizators, the secular metaphor, not the contradiction, among others, in a continued use of the resources of the computational technology. It considers changes in the proper ambience of the classroom by means of the proposal to constitute it in Atelier of Apprenticeship, where both the excessively professional professors, pupils and others education professionals act continuously as learner’s protagonists, in an interactive exchange of experiences and knowledge, constituting, thus, the Learner’s Society as the current historical context requires.